Regioselective biocatalytic self-sufficient Tishchenko-type reaction via formal intramolecular hydride transfer. Issue 47 (11th May 2020) - Tassano, Erika; Merusic, Kemal; Buljubasic, Isa; Laggner, Olivia; Reiter, Tamara; Vogel, Andreas; Hall, Mélanie
Abstract : Alcohol dehydrogenases catalyze the regioselective lactonization of dialdehydes via a bio-Tishchenko-like reaction. The nicotinamide-dependent self-sufficient reduction–oxidation sequence proceeds through a formal intramolecular hydride shift. Abstract : A self-sufficient nicotinamide-dependent intramolecular bio-Tishchenko-type reaction was developed. The reaction is catalyzed by alcohol dehydrogenases and proceeds through formal intramolecular hydride transfer on dialdehydes to deliver lactones. Regioselectivity on [1, 1′-biphenyl]-2, 2′-dicarbaldehyde substrates could be controlled via the electronic properties of the substituents. Preparative scale synthesis provided access to substituted dibenzo[ c, e ]oxepin-5(7 H )-ones.